PENGEMBANGAN KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCES) DI MADRASAH - Zainal Abidin (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Intelligence isn’t black and white there are some aspects of human intelligences not just one only. At least, there are nine types of human intelligence called multiple intelligences. Nine types of intelligence is very affecting the success of a person in the competition of life. This paper will discuss the strategy of developing multiple intelligences in madrasah as one of the Islamic educational institutions. In the reality of educational practice in madrasah shows that the priciple of multiple intelligence has long been alpied througth several materials integrated with each other. The development of potential learners in madrasah has long been developed in the several aspect of emotional, intellctual, spiritual, social and individuality intelligence in accordance with the principles of Islamic teaching.